EXPLORING POLITENESS STRATEGIES IN ‘A WALK TO REMEMBER’ MOVIE: A SOCIOLINGUISTIC APPROACH - Kasim, Hardiansyah; Satria, Robby (BASIS (Bahasa dan Sastra Inggris), 2024)
The primary objective of this research is to determine the many types of politeness tactics and the prevalent ones in the film "A Walk to Remember". This analysis aims to explore how language variation, social factors, and politeness strategies are represented through the interactions of the main characters, Jamie Sullivan and Landon Carter. Politeness tactics are used to maintain social peace and reduce communication disputes. This study uses Brown and Levinson's (1987) approach to identify several types of politeness techniques. The characters' conversation from the film "A Walk to Remember" was utilized to collect the data. The data for this study were gathered by non-participant observation and note-taking approaches. The data for this investigation were examined using a classified approach. The film screenplay had 4 examples of positive politeness, 4 instances of negative politeness, 4 instances of off-record techniques, and 4 instances of bald-on-record strategies.